THE EFFECT OF CLOUD ACCOUNTING IMPLEMENTATION, DIGITAL LITERACY, AND CYBERSECURITY AWARENESS ON FINANCIAL STATEMENT QUALITY AND AUDIT READINESS IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN INDONESIA - Rianto, Rianto; Aulia, Triana Zuhrotun; Sudarmanto, Eko (Gapenas Publisher, 2025)
This study examines the effect of cloud accounting implementation, digital literacy, and cybersecurity awareness on financial statement quality and audit readiness among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. A quantitative approach was employed with 120 respondents, using a Likert scale questionnaire (1–5) to collect data. The analysis was conducted using Structural Equation Modeling – Partial Least Squares (SEM-PLS 3) to evaluate both the measurement and structural models. The results indicate that cloud accounting implementation, digital literacy, and cybersecurity awareness each have a significant positive effect on financial statement quality. In turn, financial statement quality strongly and positively influences audit readiness. Furthermore, financial statement quality was found to partially mediate the relationship between the three independent variables and audit readiness. These findings highlight the importance of technological adoption, digital competency, and cybersecurity awareness in enhancing financial transparency and audit preparedness among MSMEs. The study provides both theoretical contributions to the digital transformation literature and practical guidance for policymakers, practitioners, and MSME managers in Indonesia.